Green Synthesis of Sulfonated Activated Carbon from Palm Kernel Shell as Potential Catalyst for Hydrolysis of Palm Bunch Cellulose - Totok Eka Suharto; Cindy Wulandari; Dwita Oktiarni; Devi Ratnawati; Ibdal Satar (CHEMICA: Jurnal Teknik Kimia, 2022)
Sulfonated activated carbon (SAC) is one of green catalysts that has been successfully synthesized from palm shell waste. The SAC catalysts have been tested in the hydrolysis of cellulose of palm bunch to simple sugar. The SAC catalysts were prepared from palm shell waste by converting to activated carbon followed by sulfonating step. The SAC catalysts were characterized by using XRD, SEM, FTIR and gravimetric methods. The SAC catalysts show as porous amorphous materials and have acidic properties, a prerequisite for good catalytic activity. Preliminary catalytic tests showed that the SAC catalysts can be used for the hydrolysis of cellulose from palm bunch waste that was shown by the existence of reducing sugar in the liquid product of hydrolysis.